Why do some consumers not charge their plug-in hybrid vehicles? Evidence from Californian plug-in hybrid owners. (5th August 2020) - Chakraborty, Debapriya; Hardman, Scott; Tal, Gil
Abstract: The environmental benefits of plug-in hybrid electric vehicles (PHEVs) are closely related to the driving and charging behavior of vehicle owners. It is often wrongly assumed that PHEV drivers plug-in once per day. Using data from drivers of the vehicles we show this is not the case and that some drivers rarely charge their PHEV. If the vehicle is not plugged-in regularly, the vehicle will drive fewer electric miles and more gasoline miles, thereby losing out on potential emission savings. Analyzing 30-day charging behavior of 5418 PHEV owners using a logistic regression model, we explore the factors that influence driver's decisions to not charge their vehicle. Several factors play a role in drivers' decision to plug-in their PHEV or not, including vehicle characteristics and the availability and cost of charging at various locations. Higher home electricity prices, lower electric driving range, lower electric motor power to vehicle weight ratios, lower potential cost savings from charging, and living in an apartment or condo, among other factors are related to not plugging in a PHEV. The findings have important implications in terms of future policy and vehicle design including which PHEVs policymakers should incentivize and what measures can encourage PHEV owners to plug-in their vehicles to help realize the environmental benefits of the technology.